Does Physical Activity Age Wild Animals? - Soulsbury, Carl D.; Halsey, Lewis G. (Frontiers in Ecology and Evolution, 2018)
There is considerable interest in why the process of ageing varies between individuals, both in humans and other animals. However, in animals, ageing in terms of survival (demographic senescence) is understood in considerably more detail than in terms of decline in the body’s functional capacity (functional senescence). Oxidative damage is probably an important component of the ageing process in many species. Oxidative stress typically increases as a result of physical activity, and many animals exhibit long and intense periods of active behaviour. These observations raise a question that has not yet been addressed: while in humans, at least, activity is considered beneficial to health, could high intensity activity play a part in the rate that wild animals age? Studies to date suggest that increased ‘effort’ can lead to reduced survival in free-living animals, but ‘effort’ refers to different processes in different studies, and is rarely clarified or quantified. To understand the role of activity in functional senescence, studies must measure the detailed activity of free-ranging animals, possibly describing it in terms of intensity, frequency and duration, coupled with records of resultant physiological and DNA damage.